LIVER TRANSPLANTATION FOR HEPATOCELLULAR CARCINOMA: EXTENSION OF INDICATIONS BASED ON MOLECULAR MARKERS - Schwartz, Myron (2008)
BACKGROUND/AIMS: Liver transplantation usually cures hepatocellular carcinoma when the Milan selection criteria are applied, whereas there is substantial risk of posttransplant recurrence with tumors beyond these criteria. This study uses molecular data to identify a subgroup of patients who, despite having hepatocellular carcinoma beyond Milan criteria, have favorable outcomes. METHODS: Allelic imbalance of 18 microsatellites was analyzed in 70 consecutive patients (35 within Milan, 35 beyond Milan criteria) transplanted for hepatocellular carcinoma of whom 24 recurred and 46 survived at least 5 years recurrence-free. Fractional allelic imbalance (the fraction of significant microsatellites that demonstrated allelic imbalance) and relevant clinical/pathological variables were tested for correlation with time to recurrence. RESULTS: Allelic imbalance in 9/18 microsatellites correlated with recurrence. Fractional allelic imbalance >0.27 and macrovascular invasion were independent predictors of recurrence in patients with tumors beyond Milan criteria; the probability of recurrence at 5 years was 85% with fractional allelic imbalance ≥0.27 vs 10% when <0.27 (p=0.0002). An algorithm including Milan criteria and fractional allelic imbalance status is 89% accurate in predicting tumor recurrence after transplantation. CONCLUSION: Analysis of allelic imbalance of 9 microsatellites identifies a subgroup of patients who, despite having hepatocellular carcinoma beyond Milan criteria, have a low risk of posttransplant recurrence.